2020
DOI: 10.3389/fendo.2020.572089
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Role of p38 Family Members in Adipose Tissue Physiology

Abstract: The complex functions of adipose tissue have been a focus of research interest over the past twenty years. Adipose tissue is not only the main energy storage depot, but also one of the largest endocrine organs in the body and carries out crucial metabolic functions. Moreover, brown and beige adipose depots are major sites of energy expenditure through the activation of adaptive, non-shivering thermogenesis. In recent years, numerous signaling molecules and pathways have emerged as critical regulators of adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 204 publications
(311 reference statements)
2
17
0
Order By: Relevance
“…Interestingly, a massive phosphorylation of p65 was observed, suggesting an additional effect of VDD and HF diet in male, as observed for inflammatory pathways and adiposity index. A significant induction of p38 phosphorylation was observed in the CTRL HF group, which is coherent since this pathway is known to be inducted during obesity [39]. Nevertheless, no impact of VDD was observed on the pathway.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Interestingly, a massive phosphorylation of p65 was observed, suggesting an additional effect of VDD and HF diet in male, as observed for inflammatory pathways and adiposity index. A significant induction of p38 phosphorylation was observed in the CTRL HF group, which is coherent since this pathway is known to be inducted during obesity [39]. Nevertheless, no impact of VDD was observed on the pathway.…”
Section: Discussionsupporting
confidence: 74%
“…Concerning molecular mechanisms, RNA seq and miRNA analysis as well as bibliography strongly converge to the putative role of NF-kB and p38/MAPK signaling pathways. Indeed, NF-kB and p38 are known to play a major role during adipose tissue inflammation [38,39]. Furthermore, we and others have demonstrated that the ability of VD to blunt inflammation in adipocytes and adipose tissue was linked to an inhibition of phosphorylation of these two signaling pathways [21,26,[40][41][42].…”
Section: Discussionmentioning
confidence: 84%
“…p38 can exert protective or deleterious roles in different cell types, which are highly dependent on the type of stimulus. Activation of p38 elicits protective effects during ischemic conditions ( Nakano et al, 2000 ; Fujimoto et al, 2004 ; Hsu et al, 2007 ) and plays an important role in the activation of brown adipose tissue ( Leiva et al, 2020 ). However, activation of p38 has been linked to inflammatory cytokine production ( Li et al, 2005 ) and ASC aging ( Zhang et al, 2020 ), and its inhibition potentiates ASC and EV therapy ( Zhang et al, 2017 ; Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the combination of hispidulin and p -synephrine resulted in a decreased protein expression of the transcription factor C/EBPβ, which plays a principal role in orchestrating early steps of adipogenesis [ 71 ]. During the early stage of adipogenesis, the nuclear localization of C/EBPβ is mediated by the activation of ERK, P38, and GR in response to adipogenic stimuli [ 72 , 73 , 74 ]. In addition, glucocorticoid hormones affect adipocyte differentiation and the maintenance of adipogenic genes by binding to GR, a ligand-activated transcription factor [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%